Penurunan mutu dan pendugaan umur simpan sup krim instan labu kuning diperkaya tempe untuk lansia dengan metode accelerated shelf life testing (ASLT) - Aulia, Salma Shafrina; Setiawan, Budi; Sinaga, Tiurma; Sulaeman, Ahmad (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Instant pumpkin cream soup enriched with tempeh had fulfilled 10% Recommended Dietary Allowances (RDA) for elderly so that it can be used as an easy-to-serve snack, but decreasing quality of instant cream soup will be happened if the instant cream soup was stored for a long time. Objectives: This study aimed to analyze quality of water content, water activity and lipid oxidation in instant pumpkin cream soup during storage and estimated the shelf life of pumpkin cream soup enriched with tempeh.Method: Â Quality storage was analyzed using of water content, water activity (aw) and lipid oxidation. Estimation of shelf life was analyzed using Arrhenius Accelerated Shelf Life Testing (ASLT) model.Results: The results showed that the water content, aw levels and lipid oxidation of instant pumpkin cream soup increased during the storage period. The critical parameter used in this study was lipid oxidation. Instant cream soup without the addition of tempeh can last 447 days Â while the cream soup with the addition of tempeh has a shelf life of 433 days.Conclusion: Quality of instant pumpkin cream soup decreased during the storage period and it would be expired over a year.